Multiscale self-assembly of a phenyl-flanked diketopyrrolopyrrole Derivative : a solution-processable building block for π‑conjugated Supramolecular polymers - Wang, Kai (2021)
We report a solution-processable π-conjugated molecular building block (denoted as PhDPP) consisting of a rigid and planar core of phenyl-flanked diketopyrrolopyrrole and “soft” branched alkoxy chains that endow the solubility in a variety of organic solvents. Intermolecular hydrogen bonding in PhDPP was revealed in nonpolar solvents above a threshold of concentration and below a critical point of temperature. The strong intermolecular interaction mainly contributed by the hydrogen-bonding and π–π interaction between PhDPP molecules promoted the formation of supramolecular polymeric structures in both solution and solid states and at interfaces. The supramolecular polymeric properties enabled solution-based processing of PhDPP under a variety of conditions into different structures including fibers and uniform thin films. The structure–property relationship that we established in the present system of PhDPP from the molecular to supramolecular level will be important to solution-process this type of H-bonding π-conjugated molecules for a variety of applications such as optoelectronic devices.